Swallowing, feeding, developmental outcomes and associated factors of South African infants with hypoxic-ischaemic encephalopathy - Van der Linde, Jeannie (University of Pretoria, 2023)
Thesis (PhD (Speech-Language Pathology))--University of Pretoria, 2023.